The Effectiveness of A Guided-Inquiry Learning Model Based On Biotechnology Practicum Materials in Improving The Learning Outcomes of High School Students - Sovia Mega Lestari; Ely Rudyatmi (FMIPA UNNES, 2023)
Prior learning of biotechnology material was carried out without the process of finding concepts by students. Learning is still centered on the teacher and does not involve student activity. So there is a need for learning that can be applied to improve understanding of concepts and student activities in learning. Theoretically, the guided-inquiry learning model can improve students understanding of concepts and active roles . The purpose of this study was to analyze the effectiveness of the guided-inquiry learning model based on biotechnology practicum material in improving high school student learning outcomes. The research design is quasi-experimental with the nonequivalent control group design. Cognitive aspects of learning outcomes were measured using multiple choice test sheets, analyzed using the N-gain test , Wilcoxon test, and Mann-Whitney test . Psychomotor aspects of learning outcomes were measured using multiple choice test sheets, analyzed using the t test; and observation sheet analyzed descriptive percentage. The teacher's response was measured with a questionnaire sheet instrument which was analyzed descriptively qualitatively. Students' responses and the implementation of learning were measured with a questionnaire sheet instrument analyzed descriptively percentage. The average N-gain cognitive aspect of the experimental class is in the medium category and the control class is in the low category. The results of learning cognitive aspects and skills based on student tests in the experimental class > control class significantly. Sixty nine percent of students are highly skilled and twenty eight percent are skilled. The teacher's response is that this guided-inquiry learning model makes it easier to emphasize concepts but there is a need for better class and time management. The response of the majority of students was good. All the learning steps of the experimental class were carried out, while in the control class the instructions recorded important points that were not conveyed. Conclusion, the guided-inquiry learning model based on biotechnology practicum materials in improving the learning outcomes of high school students.